Correlation between Programmed Learning and Metacognition: A Study on Experiential Learning Perspectives of Secondary School Teachers - Iqra Ikram; Muhammad Asim (Institute of Business Management, 2019)
This research investigated the correlation between Programmed Learning and Metacognition of students in secondary schools of Karachi from the perspectives of secondary school teachers. Literature reported that poor academic performance, lack of interest and dis-connectivity with peers among the students was the result of poorly programmed instructions of their teachers. Literature also reported the positive correlation between Programmed Learning and the development of Metacognition of students along with qualitative changes in term of self-regulated learning, social connectivity and problem-solving skills developed for the complex real world. For this quantitative research a questionnaire bearing 15 items was developed to measure the relationship between Programmed Learning and Metacognition of secondary students from Karachi. In this research the data was collected from the private English Medium schools of District South and District Center of Karachi. The participants were secondary school males and females teachers   teaching different subjects to different age group students at secondary level.  SPSS was used to calculate descriptive statistics, independent sample t-test, correlation and Regression model to predict the relationship between Programmed Learning and Metacognition of students. This study found no significant difference in the opinion of male and female teachers about Programmed Learning and Metacognition. Also, a positive and moderate high correlation (r= .693) was found between Programmed Learning and Metacognition. This research suggested academia in Pakistan to hold more researches on Programmed Learning and Metacognition in the various settings to explore the possible avenue of teaching and learning practices in B.Ed. programs for next tier of preservice and in-service teachers.